Thank you to Earth's Future Reviewers in 2018 - Ben van derPluijm; Amir AghaKouchak; Guy Brasseur; Michael Ellis; Nancy Grimm; Hong Liao; Céline H. Mari; Paty Romero‐Lankao (Earth's Future, 2019)
Abstract Peer review is one of the most important professional activities for scientists, because it ensures the quality of science that is shared with colleagues and with the world. Reviewers generously donate their time and effort with the knowledge that are key to sustaining scientific rigor. Earth's Future is fortunate to engage excellent reviewers that support the growth and reputation of our young journal as it receives and publishes high‐quality, high‐impact articles. We recognize the time, effort, and dedication that each review requires and extend a heartfelt thank you to all of our reviewers. Last year, Earth's Future received 395 peer reviews from 297 individuals that are listed below; reviewers who contributed three or more reviews are recognized in italics. Our acceptance rate remains steady at ~40%, while the number of submissions continue to increase at a healthy pace (269 in 2018). Thank you all for your important and valued contributions to our science in 2018.